Nonlinear effects and possible temperature increases in ultrasonic microscopy - Wójcik, J.; Litniewski, J.; Filipczyński, L.; Kujawska, T. (Archives of Acoustics, 2002)
Visualisation of living tissues or cells at a microscopic resolution provides a foundation for many new medical and biological applications. Propagation of waves in ultrasonic microscopy is a complex problem due to finite amplitude distortions. Therefore, to describe it quantitatively, a numerical model developed by the first author was applied. The scanning acoustic microscope operating at 34 MHz was used with strongly focused ultrasonic pulses of 4 periods. For measurements of signals, a 100 MHz PVDF probe was constructed. Its frequency characteristic was found experimentally. The numerical calculation procedure for nonlinear propagation was based on previous papers of the authors. Computations have shown that in the case under consideration, only the spectrum with an input lens pressure amplitude of 1 MPa was in agreement with the experimental one. Based on transducer power measurements, a slightly smaller pressure value was obtained thus confirming, to a good approximation, the correctness of the applied methods. A significant parameter is the ratio of the amplitudes of the second to the first calculated harmonics, which shows the extent of the nonlinearity. In our case it was equal to 0.5. After averaging over the surface of the finite electrode size used in measurements, this ratio was reduced to 0.2. Pressure distributions in the lens cavity and the following region in water were computed for the first 4 harmonics making it possible to determine many features of the nonlinear propagation effects in the microscope. Using the thermal conductivity equation and the rate of heat generation per unit volume, determined for nonlinear propagation in water, a focal temperature increase of 3.3o C was obtained. It was computed for a repetition frequency of 100 kHz. The computed temperature increases can be significant and also harmful, especially when imaging small superficial structures and testing living cell cultures. However, they can be easily decreased by reducing the repetition frequency of the microscope. The developed numerical procedure can be applied for much higher frequencies when living cells in culture are being investigated.